Serum NfL and EGFR/NfL ratio mRNAs as biomarkers for phenotype and disease severity of myelin oligodendrocyte glycoprotein IgG-associated disease - Wang, Xin; Qu, Yi; Fan, Jiayu; Ren, Huiqiang (Frontiers in Immunology, 2024)
Background and purpose: Myelin oligodendrocyte glycoprotein (MOG) IgG is frequently elevated in pediatric patients with acquired demyelinating syndrome (ADS).However, no specific biomarkers exist for phenotype classification, symptom severity, prognosis, and treatment guidance of MOG-IgG-associated disease (MOGAD). This study evaluated neurofilament light chain (NfL) and endothelial growth factor receptor (EGFR) mRNA expression levels in serum and cerebrospinal fluid (CSF) as potential biomarkers for MOGAD in Chinese children.Methods: This was a cross-sectional and single-center study. We enrolled 22 consecutive pediatric patients hospitalized with MOGAD and 20 control pediatric patients hospitalized for noninflammatory neurological diseases in Hebei Children's Hospital.Serum and CSF were collected from MOGAD patients within 3 days before immunotherapy. The mRNA levels of NfL and EGFR in serum and CSF were measured by real-time polymerase chain reaction (qPCR), and the EGFR/NfL ratio mRNA was calculated. These measurement values were then compared between disease groups and among MOGAD phenotypes. In addition, the correlations between the mRNAs of three markers (NfL, EGFR, EGFR/NfL ratio), extended disability status scale (EDSS) scores, and clinical phenotypes were analyzed.Results: Serum and CSF NfL mRNA levels were significantly higher of acute-stage MOGAD patients than those of control patients (p<0.05 and p<0.01, respectively), while the mRNA levels of serum EGFR and EGFR/NfL ratio were significantly lower of MOGAD patients than those of controls (p<0.05, p<0.0001). Serum NfL mRNA was significantly correlated with mRNA of serum EGFR (r=0.480, p<0.05). Serum and CSF NfL mRNA levels in MOGAD patients with the ADEM-like phenotype were also significantly higher than those in control patients (p<0.01, p<0.01) and optic neuritis (ON) phenotype (p < 0.05, p<0.05). Both mRNAs of NfL in CSF and EGFR/NfL ratio in serum were correlated with EDSS scores (p<0.05, r=0.251; p<0.05, r=-0.521).The mRNA levels of elevated NfL in serum and CSF as well as lower EGFR and EGFR/NfL ratio in serum could help distinguish acute-phase MOGAD. Higher mRNA levels of NfL in serum and CSF of MOGAD patients help distinguish ADEM-like phenotype. In addition, serum EGFR/NfL mRNA ratio is indicative of disease severity in pediatric patients with MOGAD. Further investigations are warranted to elucidate the pathological mechanisms underlying these associations.